Third year medical students’ perceptions of the “Values in Healthcare” selective module on their mental well-being: a pilot study from Sefako Makgatho Health Sciences University (SMU) - Tin Maung Maung, Yamin (Stellenbosch : Stellenbosch University, 2017)
Thesis (MPhil)-- Stellenbosch University, 2017.